Effect of Low Level Acute of Aflatoxin on Performance in Faw- Bro Broiler - Baghdad Science Journal (مجلة بغداد للعلوم)
This study was conducted in the Poultry farm of the animal during the Production department, Iraqi during the (Ministry of Science and Technology) period from 3-9-2001 to 8-4-2002. The objectives of this study were to evaluate the effect of low – level chronic aflatoxicosis on performance (body weight, feed conversion efficiency and mortality), Serum biochemistry and activity of some enzymes (GOT,GPT, ALKP, LDH). A total of 300 male chicks of broiler breeder (Faw–Bro) were used. Chicks at day 1 of age were fed diets contaminated with aflatoxine at levels of 0, 0.3, 0.6, 0.9, 1.2, and 1.5 the feeding period were extended to 8 weeks. The data were subjected to analysis of variance by the completely randomized design. The results showed the presence of a number of fungi especially the type of Aspergillus flavus genus that reaches 40%. All aflatoxine dose levels significantly (P < 0.05) decreased live weight, it was also noticed that there were higher significant decrease in feed conversion when aflatoxine level was elevated in the feed. Increasing mortality with each increasing in aflatoxine level, the low level of chronic aflatoxine in the diets caused increased in the relative weight of internal organs (Liver, Pancreases, spleen, heart, gizzard, fibresia gland) as a results of aflatoxine presence in the diet, the low level of chronic aflatoxicosis for long time decreased in packed cell volume percentage, heamoglbulin concentration and red blood cell cont., with increase in white blood cells and (neutrophil, Hetrophil, Lymphocyte). The aflatoxine increased the serum concentration of protein, albumin, Cholesterol, Phosphor the activity of LDH, GOT, GPT, AIKP.